Condom use and non-use among transgender women in Colombia: a qualitative analysis based on the IMB model - Jorge Eduardo Moncayo Quevedo; María Del Mar Pérez-Arizabaleta; Wilmar Hernán Reyes Sevillano (Revista de Saúde Pública, 2022)
ABSTRACT OBJECTIVE Review the reasons for condom use and non-use among transgender women in Colombia based on the information, motivation and behavioral skills (IMB) model. METHOD Qualitative study in which an iterative process analysis was carried out. A focal group participated in person, and in-depth interviews were conducted virtually. RESULTS First study carried out in Colombia on condom use among transgender women under the IMB model. The information component finds that traditional sexual education does not have a positive impact. Regarding motivational aspects, the importance of family support and follow-up and community-based organizations to motivate sexual health care and condom use is highlighted. Regarding behavioral skills, it was found that distrust towards sexual partners and the acquisition of condoms promote their use. CONCLUSIONS It is important to create spaces for sexual education delivered by and for the LGBTIQ population, followed by the medical knowledge of health centers, to have positive impacts on the sexual health of transgender women; studies with sexual partners of transgender women are encouraged in order to know the reasons why they request the non-use of condoms.